2019
DOI: 10.1016/j.jor.2019.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Racial and sex disparities in utilization rates for shoulder arthroplasty in the United States disparities in shoulder arthroplasty

Abstract: To investigate racial disparities in shoulder arthroplasty (SA), accounting for demographic factors such as sex and age. Methods: Data for SAs (2011)(2012)(2013)(2014) was queried from the Healthcare Cost and Utilization Project Nationwide Inpatient Sample. Population-adjusted SA utilization rates, racial and sex differences by age, length of stay, insurer, and comorbidities were calculated. Results: Caucasians aged 45-64 are 54% more likely than African-Americans and 74% than Hispanics to receive surgery. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…Shoulder arthroplasty is a very well-recognized and effective treatment at reducing pain and re-establishing function for many common pathologies of the shoulder. 10,28 The reproducible success and expanded indications in the setting of an increasingly older population has led to predictable increases in utilization over the decade consistent with trends from older studies. [4][5][6]10,15,24 Our study demonstrated that TSA utilization doubled from 43 per 100 000 residents in 2009 to 73 per 100 000 residents in 2017.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Shoulder arthroplasty is a very well-recognized and effective treatment at reducing pain and re-establishing function for many common pathologies of the shoulder. 10,28 The reproducible success and expanded indications in the setting of an increasingly older population has led to predictable increases in utilization over the decade consistent with trends from older studies. [4][5][6]10,15,24 Our study demonstrated that TSA utilization doubled from 43 per 100 000 residents in 2009 to 73 per 100 000 residents in 2017.…”
Section: Discussionmentioning
confidence: 95%
“…10,28 The reproducible success and expanded indications in the setting of an increasingly older population has led to predictable increases in utilization over the decade consistent with trends from older studies. [4][5][6]10,15,24 Our study demonstrated that TSA utilization doubled from 43 per 100 000 residents in 2009 to 73 per 100 000 residents in 2017. Despite that dramatic increase, our study demonstrated that disparities previously seen in joint replacement procedures persisted with over two-thirds of that annual increase being accounted for by an increase in utilization by White residents while annual utilization by Black residents were largely unchanged.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations